Undergraduate students and their views about some elements which measure the quality in higher education - Hernández-Herrera, Claudia Alejandra (Universidad Autónoma de Tamaulipas, 2019)
Providing quality education allows young people to acquire skills and develop knowledge that can facilitate their insertion into the labor market, which in turn can help them improve the quality of their life and social welfare. The aim of the paper was to analyze the perceptions of students from two institutions of higher education in Mexico regarding variables that measure quality, including the academic curriculum, faculty, extracurricular activities and tutoring, in order to determine similarities and differences and to identify areas in need of improvement. A cross-sectional and descriptive study was conducted. Data were collected through a questionnaire administered to a sample of 3 431 students. Statistical inferences were made through a factor analysis, a Mann-Whitney U test and the generalized linear models. It was found that in the case of the Instituto Politécnico Nacional (IPN), undergraduate students of industrial management had a positive perception of the curriculum, unlike those majoring in technology related areas who rated it low. It was also found that the IPN students who do not have a job value the work of the faculty members more than those who do. In contrast, the TecNM students who indicated that they are in the labor market gave their faculty higher ratings. The article concludes by highlighting that both institutions work under different conditions. However, it also stresses the need for the two of them to engage in further efforts to change the perception that students have about the various areas that evaluate the quality of  education.